Canadian Recommendations for Critical Care Ultrasound Training and Competency - Robert T Arntfield; Scott J Millington; Craig D Ainsworth; Rakesh C Arora; John Boyd; Gordon Finlayson; William Gallagher; Colin Gebhardt; Alberto Goffi; Edgar Hockmann; Andrew W Kirkpatrick; Robert C McDermid; et al. (Canadian Respiratory Journal)
OBJECTIVE: To achieve national consensus on standards of training, quality assurance and maintenance of competence for critical care ultrasound for intensivists and critical care trainees in Canada using recently published international training statements.